2009
DOI: 10.1007/s00421-009-1205-4
|View full text |Cite
|
Sign up to set email alerts
|

Resting state networks in human cervical spinal cord observed with fMRI

Abstract: It has been reported that spontaneous fluctuations of blood oxygen level dependent (BOLD) signals can be detected in human brain and constitute resting state networks. It has not been reported whether resting state networks also exist in human spinal cord. In the present study, we investigate spontaneous BOLD signal changes in human cervical spinal cord during resting state. fMRI data were analyzed with independent component analysis and SPM software package. Acceptable reproducibility of spatial maps of BOLD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Spinal cord fMRI has primarily been used to study motor and sensory/pain pathways in the healthy spinal cord, but has also been shown to be sensitive to changes in patients with spinal cord injury (Stroman et al, 2002, 2004; Kornelsen and Stroman, 2007) and multiple sclerosis (Agosta et al, 2008a, 2008b, 2009b; Valsasina et al, 2010, 2012). Importantly, these spinal fMRI studies were focused on understanding spinal cord function when performing tasks, and to date only one paper has reported an investigation of resting state BOLD fluctuations in the human spinal cord, from which the results were equivocal (Wei et al, 2010). Partly, the lack of positive reports may reflect the relatively poor signal-to-noise ratio of spinal cord images achievable at conventional field strengths (1.5 Tesla and 3.0 Tesla) and the inherent limitations of low spatial resolution in studying small structures.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord fMRI has primarily been used to study motor and sensory/pain pathways in the healthy spinal cord, but has also been shown to be sensitive to changes in patients with spinal cord injury (Stroman et al, 2002, 2004; Kornelsen and Stroman, 2007) and multiple sclerosis (Agosta et al, 2008a, 2008b, 2009b; Valsasina et al, 2010, 2012). Importantly, these spinal fMRI studies were focused on understanding spinal cord function when performing tasks, and to date only one paper has reported an investigation of resting state BOLD fluctuations in the human spinal cord, from which the results were equivocal (Wei et al, 2010). Partly, the lack of positive reports may reflect the relatively poor signal-to-noise ratio of spinal cord images achievable at conventional field strengths (1.5 Tesla and 3.0 Tesla) and the inherent limitations of low spatial resolution in studying small structures.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a stimulus or task, fluctuations in neuronal activity in the spinal cord have been detected by means of functional MRI, and are thought to provide important information about networks of regions across the CNS [24]. However, due to methodological challenges very few “resting-state” fMRI studies have been carried out in the spinal cord and no specific networks have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to methodological challenges very few “resting-state” fMRI studies have been carried out in the spinal cord and no specific networks have been identified. It has been speculated that the source of resting-state fluctuations (RSF) may be linked to brain resting-state networks, muscle coordination, and/or descending regulation of sensory signaling [24]. Smith and Kornelsen [5] showed variations in blood oxygenation-level dependent (BOLD) fMRI signal in the cord when participants viewed negative, positive, and neutral pictures from the International Affective Picture System (IAPS) database.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct spatial maps due to cardiac and respiratory noise sources have been revealed by single subject ICA (25)(26)(27), and a seed-based approach demonstrated correlations between ventral horns and between dorsal horns (28), but no group patterns of circumscribed motor or sensory networks have yet been found; also only a few investigations of task-based functional connectivity have been performed (29)(30)(31). One reason for the apparent lack…”
mentioning
confidence: 99%